The Influence of Office Employees’ Eating Behaviour Due to Stress: The Case of Universiti Malaysia Sabah Office Employees - Dg. Khairunisa Ahmad Sapawi; Ng Hui Ming (Bulletin of Culinary Art and Hospitality, 2021)
It is common for stressful people to seek relief through eating their favourite foods or comfort foods. However, these foods can be unhealthy if taken too frequently. The study focuses on determining the university office employees’ choice of comfort foods and investigating the influence of stress on their eating behaviours. Among all of Universiti Malaysia Sabah office employees, 337 were selected through stratified sampling. Self-administered questionnaires were used to collect data. Descriptive and one-way ANOVA analysis were used. Findings showed most respondents were within medium level of stress. Based on the findings of IES, the differences on stress levels on respondents’ comfort food intake were significant (F (2, 334) =8.71, p lower than 0.05). However, respondents are found to enjoy consuming comfort foods regardless of stress levels and will choose comfort foods to satisfy hunger. This highlights the importance of diet intervention to be included as a component in stress management as to aid the prevention of diet-related diseases among the university office employees.